2017
DOI: 10.15761/jto.1000117
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal delivery of bone marrow stem cells in ALS: A preliminary report

Abstract: Introduction: There is no effective therapy for amyotrophic lateral sclerosis (ALS). Safety and feasibility of intrathecal autologous stem cell injections in ALS patients is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The system has three facets: the first remembers the taking of medications, the second measures the emotional state of the subjects focuses mainly in electroencephalography (EEG), the third proposes exercises based on the previous determination of the emotional state. In [2] the purpose is to detect the state of relaxation based on physiological signals, specifically in the galvanic skin response (GSR), also called electrodermal activity (EDA). In [3] an experiment is carried out to measure stress in real life, where 16 subjects participate.…”
Section: Review Of the State Of The Artmentioning
confidence: 99%
“…The system has three facets: the first remembers the taking of medications, the second measures the emotional state of the subjects focuses mainly in electroencephalography (EEG), the third proposes exercises based on the previous determination of the emotional state. In [2] the purpose is to detect the state of relaxation based on physiological signals, specifically in the galvanic skin response (GSR), also called electrodermal activity (EDA). In [3] an experiment is carried out to measure stress in real life, where 16 subjects participate.…”
Section: Review Of the State Of The Artmentioning
confidence: 99%
“…In another study by Prabhakar et al, stabilization of disease was observed, with no significant decline in ALS FRS-R score over a one-year follow-up duration, following intrathecal administration of autologous bone marrow derived stem cells [14]. A study by Martinez et al suggested slower disease progression in ALS patients during a one year follow up post intrathecal transplantation of bone marrow derived mononuclear cells [105]. In this study, a total decrease of 4 points in the ALS FRS-R score at one year was noted against the usual average decline of 13.32 points.…”
Section: Clinical Studiesmentioning
confidence: 99%